Encapsulamento e caracterização de nanopartículas de Y2O3 : Nd3+ para aplicação como nanotermômetros - Domingos, Lorena Feitoza Aragão (2022)
Inorganic nanoparticles prepared with sizes similar to biomolecules can be used to develop new biological sensors for in vivo and in vitro investigation. For this type of application, it is necessary to obtain a stable colloidal dispersion of those nanoparticles in water. Therefore, inorganic nanoparticles must have their surfaces modified to acquire hydrophilic character without prejudice to their properties. In this sense, the present work investigated the synthesis, encapsulation and characterization of yttrium oxide nanoparticles (Y2O3) doped with neodymium ions (Nd3+) for applications in optical thermosensors. To measure temperature on a submicrometer scale, contact thermometers are not suitable, so the development of noninvasive methods for thermometry, luminescent nanothermometry, has been stimulated. Luminescent thermometry aims to monitor deeper tissues. The nanoparticles were prepared by a modified sol-gel route. In this route, the chelating capacity of natural humic substances present in river water was used to polymerize the metallic solution. In this work, nanoparticles treated at 450 and 1000 °C were synthesized in order to obtain different crystallite sizes, and with that to study the influence of crystallite size on material sensing, an important point for the application. After that, the nanoparticles were encapsulated by a triblock polymer that has a hydrophobic character at the center of the chain and hydrophilic at the ends, following a temperature-induced phase transition methodology. Then, the samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FTIR), optical absorption (AO) and temperature dependent luminescence. With the diffraction pattern of the Y2O3:Nd nanoparticles, it was possible to estimate the average size of the crystallites, which is 11 when the nanoparticle is treated at 450 °C and 37 nm for the sample treated at 1000 °C. It was observed, in the SEM images, particles with irregular shapes, with a wide distribution of sizes and agglomerates. In order to observe the influence of encapsulation for the desired application, measurements of encapsulated and non-encapsulated samples were performed. With the DLS measurements, particles with a size distribution around 1 μm after being encapsulated were verified. In addition, a very intense luminescence signal was detected for the non-encapsulated and encapsulated samples when they were excited by an 800 nm CW laser diode. And the values of the relative sensitivity (Sr) of the Y2O3:Nd encapsulated nanocrystals indicate the potential of these materials for temperature sensing at the nanoscale.